Design and Development of Control Systems for an Aircraft. Comparison of Performances Through Computational Simulations - Urrea-Onate, E; Venegas-Fernandez, D (IEEE Computer Society, 2018)
The main objective of this paper is to evaluate the technical aspects of the different controllers (PID, MPC and Neural) for the performance of an aircraft s behavior in relation to the longitudinal equations investigated. For this purpose, the behavior of these controllers was developed in a simulator to compare the performance of each one and to be able to decide which is the most advisable according to reference values. The development strategy is to conduct research to determine the various factors such as equations that will help us determine the correct analysis. © 2003-2012 IEEE.